2011
DOI: 10.1097/bpo.0b013e318223b575
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Legg-Calvè-Perthes Disease

Abstract: Even after 100 years, problems of early evaluation, classification, and treatment of Legg-Calvè-Perthes disease (LCPD) are still under discussion. In the past, most of the studies on the natural history of LCPD proved that majority of the cases heal spontaneously without functional impairment at maturity, but if we consider the late results a considerable number of hips become painful and require prosthesis. Thus, in this review the results of the several important papers published in the last 40 years and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(25 reference statements)
0
6
0
1
Order By: Relevance
“…11,22 Gadoliniumenhanced MRI is a sensitive modality for diagnosing LCPD at the early stages of the disease, with accuracy comparable to bone scintigraphy. 14 However, gadolinium-enhanced MRI can provide a greater accuracy in depicting necrosis and revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…11,22 Gadoliniumenhanced MRI is a sensitive modality for diagnosing LCPD at the early stages of the disease, with accuracy comparable to bone scintigraphy. 14 However, gadolinium-enhanced MRI can provide a greater accuracy in depicting necrosis and revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors speak of true containment in MRI. 26 , 27 With MRI, not only is an early diagnosis of LCPD possible, 11 so is an early determination of the loss of containment. Arthrography and MRI reveal a loss of containment, although it was not detectable in conventional X-ray photography.…”
Section: Discussionmentioning
confidence: 99%
“…Since the anterior femoral head is more often involved, sagittal images most accurately depict the full extent of involvement (74). Studies have shown that MR imaging can be used to detect early growth plate involvement (75), and the development of transphyseal enhancement is a risk factor for bridge formation (76). Poor prognostic indicators include older patient age (>7 years) at disease onset (77), severe head deformity (78), lateral pillar collapse (67), growth plate involvement (79,80), and metaphyseal lesions (71).…”
Section: Legg-calvé-perthes Diseasementioning
confidence: 99%